Reliability Assessment of Wind Turbine Monopile Foundations based on Possibility Approach integrating Local Experience and External Database - Stefanini, Luciano; Dobbs, Marcus R.; Tombari, Alessandro; ICASP14 (My University, 2023)
Reliability Analysis based on probabilistic methods is widely applied in geotechnical engineering. Several analytical and numerical methods have been developed to assess reliability based on the concept of occurrence of failure. Nevertheless, the critical aspect involves the input data used for performing these analyses. Common geotechnical engineering real-world problems deal with scarce and sparse information due to the lack of experimental data, which are not available to a sufficient extent and quality to be used to infer a reliable probability distribution. Therefore, non-probability and hybrid methods based on fuzzy logic and possibility theory as well as imprecise probabilities, have been proposed. In this paper, a methodology based on the possibility approach has been extended to account for an external local database to support the reliability assessment of a monopile foundation of an offshore wind turbine. First, a specific cardinality based on the membership function of the fuzzy limit state is proposed to assess the fuzzy reliability. The target cardinality is calibrated to be consistent with the Level II reliability method if data were of ideal random nature. Secondly, fuzzy clusterization is carried out to determine fuzzy partitions to be used for the computation of the fuzzy limit state. The number of subclasses is related to a specific degree of understanding; therefore, the proposed method integrates the practitionerﾒs local experience for finalizing the decision-making process and assessing the reliability of the geotechnical problem. Practical examples of reliability assessment of wind turbine monopile foundations are provided to highlight the potentiality of the proposed methodology.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED